2004
DOI: 10.1074/jbc.m313433200
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent Anion-selective Channels VDAC2 and VDAC3 Are Abundant Proteins in Bovine Outer Dense Fibers, a Cytoskeletal Component of the Sperm Flagellum

Abstract: Outer dense fibers (ODF) are specific subcellular components of the sperm flagellum. The functions of ODF have not yet been clearly elucidated. We have investigated the protein composition of purified ODF from bovine spermatozoa and found that one of the most abundant proteins is a 30 -32-kDa polypeptide. This protein was analyzed by sequencing peptides derived following limited proteolysis. Peptide sequences were found to match VDAC2 and VDAC3. VDACs (voltage-dependent, anion-selective channels) or eukaryotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 48 publications
7
110
0
1
Order By: Relevance
“…Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is a cytosolic protein in somatic cells, which is found to be associated with the mitochondria in the mature spermatozoa (50). On the other hand, Voltage-dependent anion-selective channels (VDAC2 and VDAC3), which are mitochondrial porins in somatic cells, are found to be associated with the cytoskeletal elements (outer dense fibers) in the bovine sperm flagella (60). It is obvious that such dramatic changes in localization probably imply fulfillment of specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is a cytosolic protein in somatic cells, which is found to be associated with the mitochondria in the mature spermatozoa (50). On the other hand, Voltage-dependent anion-selective channels (VDAC2 and VDAC3), which are mitochondrial porins in somatic cells, are found to be associated with the cytoskeletal elements (outer dense fibers) in the bovine sperm flagella (60). It is obvious that such dramatic changes in localization probably imply fulfillment of specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…mice were generated. VDAC1 deficient mice are viable and show that mitochondrial functions are slightly affected; VDAC2 gene deletion is lethal [14]; the spermatozoa are rich in VDAC3 [15]: mice lacking VDAC3 are healthy, but males are infertile [16].…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies have reported that VDAC is present in mammalian spermatozoa and plays putative roles in spermatogenesis, sperm maturation and fertilization [15][16][17][18][19]. However the respective expression, localization and function of three VDAC subtypes remain uncertain.…”
Section: Introductionmentioning
confidence: 99%